Youth in interfaith dialogue: Intercultural understanding and its implications on education in the Philippines - Cornelio, Jayeel (Archīum Ateneo, 2012)
In the wake of religious conflicts around the world, interfaith dialogues are being introduced to facilitate intercultural and religious understanding and tolerance. Although the participation of young people in interfaith dialogue and its impact on education is crucial to its sustainability, the literature on youth and interfaith has been very limited. This article addresses this gap by probing the significance or impact of interfaith on the views of our youth respondents on other religions. The view of our youth respondents show that interfaith dialogues do not have to begin and end in theological discussions. To them, the significance of interfaith revolves around the person (and not his or her religion), friendships, and collective participation in the community. We use these insights to reflect on their possible implications on the conduct of education in the Philippines. Three areas are explored: the necessity of interfaith dialogue within education, the feasibility of implementing it in the classroom, and its potential for youth empowerment. The article draws from interviews with the members of the Muslim-Christian Youth for Peace and Development (mcypd), an interfaith community based in a neighborhood in Metro Manila